Corporate bankruptcy prediction in Poland against the background of foreign experience - Błażej Prusak (e-Finanse: Financial Internet Quarterly, 2019)
In highly developed countries, research in the field of bankruptcy risk prediction has been conducted for many years. For example, in the United States, which can be considered a pioneering country, the first publications appeared in the early twentieth century. In Poland, due to political and economic reasons, the interest in this issue dates back to the early 1990s. For this reason, this publication attempts to answer the following questions: 1) What is the level of advancement of the research into predicting bankruptcies of enterprises in Poland? 2) How does it compare to worldwide trends? Therefore, the main aim of this study is to present and evaluate the scientific achievements of Polish authors in the field of corporate bankruptcy prediction and compare them to global trends. Literature analysis was adopted as the research method and shows that initially in Poland only very simple tools were used to assess the risk of bankruptcy of enterprises. With time, however, advanced methods began to be introduced and new models included non-financial variables. Also, research on the selection of the samples was conducted. Currently, the level of research and applied tools do not differ from those used in highly developed countries.
Keywords: G33; G17; 330; corporate bankruptcy; prediction; insolvency risk